2019
DOI: 10.1109/access.2019.2903229
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment for Discrete Stochastic Time-Cost-Quality Trade-Off Problem Using Simulation-Based Integer Linear Programming Approach

Abstract: Time, quality, and cost are the most critical performance indicators in project management. It has always been considered a tough challenge for project managers to optimize them simultaneously. This paper aims at establishing a simulation-based integer linear programming tool that helps project managers, at the preliminary stages, to assess the risks related to the feasibility and profitability of the projects within the framework of a stochastic discrete time-cost-quality tradeoff problem. The computational e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…They used multi-objective optimization of Non-Dominated Sorting Genetic Algorithms (NSGA-II). Mrad et al ( 2019 ) suggested a Mixed Integer Linear Programming (MILP) for TCQTP. They considered the project budget as a constraint.…”
Section: Survey On Related Workmentioning
confidence: 99%
“…They used multi-objective optimization of Non-Dominated Sorting Genetic Algorithms (NSGA-II). Mrad et al ( 2019 ) suggested a Mixed Integer Linear Programming (MILP) for TCQTP. They considered the project budget as a constraint.…”
Section: Survey On Related Workmentioning
confidence: 99%
“…Mrad et al [13] developed a simulation-based integer linear programming (LP) tool to help project managers, in evaluating risks that associated with the profitability and feasibility of the projects in the framework of a stochastic discrete TCQT problem through integrating the integer linear programming with MCS tool, which allows to evaluate risks related to duration, cost and also quality. In the project management area, the aforementioned approach can support decision makers to choose the best and most valuable project among many potential alternatives based on the risks related to their cost, duration, and quality.…”
Section: Time-cost Trade Offmentioning
confidence: 99%
“…Although decreasing project duration results in saving the indirect costs of the project, it also result in increasing the direct costs which leads to tradeoff problem shouldn't be overlooked. Consequently, Several practitioners and researchers have studied TCT analysis problem using various techniques with Artificial Intelligence (AI) [7] and also adding different dimensions to the problem such as quality [8] [9], environmental impact [10], safety [11], or incorporating risk to the problem [12], [13] In this paper, recent improvements in TCT, RSPs and interrelationships between them, using a state of art review for most recent articles related to two selected topic. The paper is structured as following; Section 2 describes research methodology, Section 3 displays discussion, however Section 4 illustrates content analysis, and finally, Section 5 demonstrates the conclusion of article and opportunities for future research.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Gardner (2020), where it focus on understanding the trade-off between feedback on conformance quality and production speed, a slack in resources which represents cost to an organization is also regarded as a trade-off relation and is inherent to or inevitable in a process (Madapusi and D'Souza, 2012;Parast, 2011). When the impact of a decision on each of the performance dimensions are then involved, it is also a trade-off relation (Rosenzweig and Easton, 2010;Mrad et al, 2019). This systemic view is recognized by managers at a strategic level but not evident in operational decisions.…”
Section: Trade-off and Unbalanced Systems Relationshipmentioning
confidence: 99%